New Labour and the Civil Service - Richards, D. author. aut Link
XII, 272 p.
Keywords: This is the first serious study to analyze Labour's approach to the Civil Service. It offers a theoretically engaged, empirically rich analysis drawing from over 300 interviews with key actors to explore the 'New Labour' effect on Whitehall. It considers 1997 transition process and the extent to which reform has improved public service delivery.